1980
DOI: 10.1111/j.1365-2621.1980.tb03864.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Calcium Salts for Soybean Curd Preparation

Abstract: One of the delicate steps in the preparation of soybean curd is the addition of a salt to precipitate soy protein. The commonly employed salt is calcium sulfate. In this study, the use of other calcium salts (calcium chloride, calcium lactate, calcium acetate, calcium carbonate, calcium phosphate, calcium hydroxide, calcium gluconate) and two noncalcium compounds (gluconod-lactone and acetic acid) was'investigated. The result showed that soy protein was pfecipitated by calcium chloride, calcium lactate, calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
54
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 2 publications
9
54
1
Order By: Relevance
“…Assays 1, 9, and 13 resulted in tofu protein contents above commercial tofu range, which is an advantage from the nutritional point of view. These results agree with those in the literature, which varied from 4.5 (ROSSET, 2007) to 12.2 g protein.100 g -1 tofu (LIM et al, 1990), while Lu et al (1980), Cai et al (1997), Cai and Chang (1998), and Min, Yu and Sant Martin (2005) found intermediate values.…”
Section: Effects Of the Factors On The Responsessupporting
confidence: 83%
“…Assays 1, 9, and 13 resulted in tofu protein contents above commercial tofu range, which is an advantage from the nutritional point of view. These results agree with those in the literature, which varied from 4.5 (ROSSET, 2007) to 12.2 g protein.100 g -1 tofu (LIM et al, 1990), while Lu et al (1980), Cai et al (1997), Cai and Chang (1998), and Min, Yu and Sant Martin (2005) found intermediate values.…”
Section: Effects Of the Factors On The Responsessupporting
confidence: 83%
“…11) It has been proposed that the first step in making tofu is the formation of a network of protein particles at a low calcium concentration, with subsequent binding of soluble proteins into the network due to the further addition of calcium and decreasing pH value. 8) Although the correlation between the yield and textural properties of tofu and the coagulant concentration has been widely reported, 10,[12][13][14][15][16][17][18][19][20][21][22] the difference in intermolecular interaction between silken tofu and regular tofu has not been elucidated. It has been found difficult to compare the difference of initiating protein concentration between silken tofu and regular tofu in the industrial process.…”
mentioning
confidence: 99%
“…Wang and Cavins (1989) found similar values of moisture (87.3%), total solids (12.7%) and fat (4.1%). Tofu is considered a precipitated soy protein and its clotting begins at a pH of approximately 6.0 (Lu et al, 1980;Knorr, 1984). In the present investigation, the pH varied between 6.13 and 6.20.…”
Section: Resultsmentioning
confidence: 99%